Tissue factor is unregulated in microvascular endothelial cells of patients with heart failure - Reichman-Warmusz, Edyta; Domal-Kwiatkowska, Dorota; Matysiak, Natalia; Kurek, Józef; Spinczyk, Dominik; Dudek, Damian; Helewski, Krzysztof; Wojnicz, Romuald (Journal of clinical pathology, 2016)
AimsSeveral lines of evidence point to hypercoagulability as an important factor for heart failure (HF) pathogenesis.MethodsWe hypothesised that endothelial tissue factor (TF) expression reflects altered tissue haemostasis which is related to the severity of HF. Accordingly, we investigated TF expression in the biopsies of 60 patients with HF and 22 without HF. In addition, we assessed the relationship between endothelial TF expression and clinical markers of HF severity.ResultsThe control subjects without HF presented absent or weak TF expression in few microvessels, while the endomyocardial biopsies of patients with HF, capillary vessels presented both weak and severe staining patterns by immunohistochemistry usually with regional distribution. This was collaborated by the immune electron microscopic study. The severe microvessel TF antigen expression was found in 11 (18.3%) patients with HF. The endothelial TF expression was inversely associated with left ventricular ejection fraction (r=−0.42, p=0.001) and positively with N-terminal brain natriuretic peptide (r=0.36, p<0.023), markers of HF severity.ConclusionsRegional upregulation of the TF in the capillary endothelial cells suggests local myocardial thrombogenicity. Furthermore, the relationship between endothelial TF and HF severity would be keeping in line with the hypothesis that an altered tissue haemostasis is most profoundly expressed in patients with severe HF. Weak TF expression found in several microvessels of the biopsy specimens patients without HF pathology might be potentially related to a low basal level of activation of the clotting system in normal individuals.